An Interface-Capturing Method for Resolving Compressible Two-Fluid Flows with General Equation of State (Communications in Computational Physics, 2020)
In this study, a stable and robust interface-capturing method is developedto resolve inviscid, compressible two-fluid flows with general equation of state (EOS).The governing equations consist of mass conservation equation for each fluid, momentumand energy equations for mixture and an advection equation for volume fractionof one fluid component. Assumption of pressure equilibrium across an interface isused to close the model system. MUSCL-Hancock scheme is extended to constructinput states for Riemann problems, whose solutions are calculated using generalizedHLLC approximate Riemann solver. Adaptive mesh refinement (AMR) capability isbuilt into hydrodynamic code. The resulting method has some advantages. First, it isvery stable and robust, as the advection equation is handled properly. Second, generalequation of state can model more materials than simple EOSs such as ideal andstiffened gas EOSs for example. In addition, AMR enables us to properly resolve flowfeatures at disparate scales. Finally, this method is quite simple, time-efficient and easyto implement.